Date-stamping US housing market explosivity - Mehmet Balcilar; Nico Katzke; Rangan Gupta (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper the authors set out to date-stamp periods of US housing price explosivity for the period 1830-2013. They make use of several robust techniques that allow them to identify such periods by determining when prices start to exhibit explosivity with respect to its past behaviour and when it recedes to long term stable prices. The first technique used is the Generalized supADF (GSADF) test procedure developed by Phillips et al. (Testing for multiple bubbles: Historical episodes of exuberance and collapse in the S&P 500, 2011a), which allows the recursive identification of multiple periods of price explosivity. The second approach makes use of Robinson's test statistic (Efficient tests of nonstationary hypotheses, 1994), comparing the null of a unit root process against the alternative of specified orders of fractional integration. The analysis date-stamps several periods of US house price explosivity, allowing the authors to contextualize its historic relevance.
Keywords: C22; G15; G14; 330; GSADF; bubble; structural breaks; random walk; explosivity; recursive process